Grin2b 3’UTR is necessary for synaptic plasticity and spatial learning - Alex C. Harvey; Ulrik Bølcho; Bevan S. Main; Anders Nykjær; Mai Marie Holm; Poul Nissen; Magnus Kjærgaard; Hanne Poulsen (Proceedings of the National Academy of Sciences, 2026)
Spatially precise protein synthesis is critical for synaptic plasticity and cognitive function. The GRIN2B transcript encodes the GluN2B subunit of N-methyl-D-aspartate (NMDA) receptors and has a 25 kb-long 3’-untranslated region (3’UTR) of unknown function. To investigate its role, we generated a ∆3’UTR mouse line by deleting the Grin2b 3’UTR while preserving the coding sequence. Despite unchanged Grin2b mRNA levels in ∆3’UTR mice, GluN2B protein was reduced 50%. In wildtype (WT) mice, Grin2b mRNA was enriched in synaptosomes, but this enrichment was impaired in ∆3’UTR mice along with reduced GluN2B phosphorylation. Notably, ∆3’UTR mice had no long-term potentiation (LTP) and exhibited hippocampal-dependent spatial learning impairments. Together, these findings demonstrate that the 3’UTR is critical for Grin2b mRNA function, ultimately influencing synaptic composition and plasticity.